WHAT DOES IT DEPEND ON TO ENSURE THE CONTINUITY OF ELECTRICITY CONSUMPTION - Yulchiev Mash’albek Erkinovich; Xasanov Sirojiddin (Лучшие интеллектуальные исследования, 2024)
Annotation. Electricity is becoming one of the urgent problems of today. It should be noted that it is impossible to imagine life without electricity. All technical processes from the production of electricity to the end of its delivery to the consumer are of great importance.